Examining public health crises: Arizona hotspots and neighborhood-level predictors of homicide, suicide, and overdose - Jordan Batchelor; Laura Lightfoot; Christi L. Gullion; Charles M. Katz (Applied Geography, 2026)

Population genomics of invasive Gomphocarpus fruticosus in Australia points to the need for taxonomic research in the native range - Karen L. Bell; Kathryn L. Batchelor; Mariana Campos (Biological Invasions, 2025)

Nutrition and Acute Myeloid Leukemia and Myelodysplastic Syndromes in Older Adults (Aged ≥60): A Scoping Review - Victoria Crowder; Ayomide Okanlawon Bankole; Jamie L. Conklin; Amanda S. Sawyer; Amanda M. Holliday; Rebecca Fogle; Lorinda A. Coombs; Daniel R. Richardson; Melissa Batchelor; Anna Beeber; Todd Schwartz; Ashley Leak Bryant (Journal of the Academy of Nutrition and Dietetics, 2025)

Stad Slide: Preconditioning and failure of one of the world's largest megaslides - B. K. Tiller; C. L. Batchelor; B. Bellwald; B. Manton; K. Winter; N. Ross; S. Planke (Journal of Quaternary Science, 2025)
Submarine landslides can generate tsunamis and pose risks to underwater infrastructure, but a lack of direct observations of such slides hinders our understanding of their development and hazard potential. Studying the morphology of past slides can offer insights into their preconditioning and failure. Here, new high‐quality 2D and 3D seismic data were used to determine, for the first time, the extent and morphology of the Stad Slide (~0.4 Ma) on the northeast Atlantic margin. With a volume of ~4300 km 3 and a maximum thickness of ~360 m, we reveal that this slide is the largest by volume on the proximal North Sea Fan and amongst the largest known megaslides globally. Its large volume was likely facilitated by retrogressive development along layers of glacimarine and contouritic sediment. The broad timing of the Stad Slide aligns with enhanced glacial sedimentation in this region, which is likely to have preconditioned failure by increasing overpressure in underlying sediments. The slide headwalls are infilled by an ~200 m‐thick contourite drift that may have formed the weak layer for subsequent sliding on the North Sea Fan.

Shelf-break glaciation and an extensive ice shelf beyond northwest Greenland at the Last Glacial Maximum - Christine L. Batchelor; Diana W. Krawczyk; Elaina O'Brien; Joyce Mulder (Marine Geology, 2024)

Neuropsychological Deficits in Disordered Screen Use Behaviours: A Systematic Review and Meta-analysis - Michoel L. Moshel; Wayne A. Warburton; Jennifer Batchelor; Joanne M. Bennett; Katherine Y. Ko (Neuropsychology Review, 2024)
Over the last few decades, excessive and disordered screen use has become more prevalent, prompting investigations into its associated consequences. The extent to which disordered screen use behaviours impact neuropsychological functioning has been reportedly mixed and at times inconsistent. This review sought to synthesise the literature and estimate the magnitude of overall cognitive impairment across a wide range of disordered screen use behaviours. We also sought to determine the cognitive domains most impacted, and whether the observed impairments were moderated by the classification of screen-related behaviours (i.e., Internet or gaming) or the format of cognitive test administration (i.e., paper-and-pencil or computerised). A systematic search of databases (Embase, PsycINFO, MEDLINE) identified 43 cross-sectional articles that assessed neuropsychological performance in disordered screen use populations, 34 of which were included in the meta-analysis. A random-effects meta-analysis revealed significant small/medium ( g = .38) cognitive deficits for individuals with disordered screen use behaviours relative to controls. The most affected cognitive domain with a significant medium effect size ( g = .50) was attention and focus followed by a significant reduction in executive functioning ( g = .31). The classification of disordered screen use behaviours into Internet or gaming categories or the format of cognitive testing did not moderate these deficits. Additionally, excluding disordered social media use in an exploratory analysis had little effect on the observed outcomes. This study highlights a number of methodological considerations that may have contributed to disparate findings and shows that disordered screen use can significantly impact cognitive performance. Recommendations for future research are also discussed. Data for this study can be found at https://osf.io/upeha/ .

Movement beyond the mean: decoupling sources of individual variation in brook trout movement across seasons - Shannon L. White; Jason Keagy; Sarah Batchelor; Julia Langlois; Natalie Thomas; Tyler Wagner (Environmental Biology of Fishes, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Maternal Nanomaterial Inhalation Exposure: Critical Gestational Period in the Uterine Microcirculation is Angiotensin II Dependent - Krista L. Garner; Elizabeth C. Bowdridge; Julie A. Griffith; Evan DeVallance; Madison G. Seman; Kevin J. Engels; Caroline P. Groth; William T. Goldsmith; Kim Wix; Thomas P. Batchelor; Timothy R. Nurkiewicz (Cardiovascular Toxicology, 2022)

Aerial photography and dendrochronology as tools for recreating invasion histories: do they work for bitou bush (Chrysanthemoides monilifera subsp. rotundata)? - John K. Scott; Kathryn L. Batchelor; Tommaso Jucker; Bruce L. Webber (Biological Invasions, 2019)

Quaternary evolution of the northern North Sea margin through glacigenic debris‐flow and contourite deposition - Christine L. Batchelor; Dag Ottesen; Julian A. Dowdeswell (Journal of Quaternary Science, 2017)
The Norwegian Channel Ice Stream of the Scandinavian Ice Sheet extended across the northern North Sea margin during the mid‐ to late Quaternary, eroding older sediment from the continental shelf. Consequently, little is known about early Quaternary sedimentation on this margin. We use two‐ and three‐dimensional seismic‐reflection data to investigate changing sediment volumes and sources in the northern North Sea through the Quaternary. The northern North Sea Basin was infilled during the early Quaternary by intercalated glacigenic debris‐flows and contourites, which provide a record of the delivery of glacigenic sediment to the slope and the intensity of North Atlantic thermohaline circulation during early Quaternary glacial–interglacial cycles. The infilling of the basin reduced accommodation and led to the deflection of mid‐ to late Quaternary sediments into the Norwegian Sea, forming the North Sea Fan. Close to the onset of the mid‐Quaternary, the south‐western Scandinavian Ice Sheet margin was drained by an ice stream located beneath Måløy Plateau, 60 km east of the Last Glacial Maximum Norwegian Channel Ice Stream. The southward‐flowing Norwegian Sea Bottom Water current was directed into the partially filled northern North Sea Basin during the early Quaternary, and deflected progressively northwards as the basin became infilled.

Restoration of Riparian Areas Following the Removal of Cattle in the Northwestern Great Basin - Jonathan L. Batchelor; William J. Ripple; Todd M. Wilson; Luke E. Painter (Environmental Management, 2015)

Pesticide Application and Detection in Variable Agricultural Intensity Watersheds and Their River Systems in the Maritime Region of Canada - Zisheng Xing; Lien Chow; Art Cook; Glenn Benoy; Herb Rees; Bill Ernst; Fanrui Meng; Sheng Li; Tianshan Zha; Clair Murphy; Suzanne Batchelor; L. Mark Hewitt (Archives of Environmental Contamination and Toxicology, 2012)

Genetic Stability in Potato Germplasm for Resistance to Root Galling Caused by the Pathogen Spongospora subterranea - Nadav Nitzan; Kathleen G. Haynes; Jeff S. Miller; Dennis A. Johnson; Tom F. Cummings; Dallas L. Batchelor; Chris Olsen; Charles R. Brown (American Journal of Potato Research, 2010)

The presence of Zygina sp. and Puccinia myrsiphylli reduces survival and influences oviposition of Crioceris sp. - Helen Spafford Jacob; Thomas E. Reilly; Kathryn L. Batchelor (BioControl, 2007)

Changes in intracellular free amino acids in tissues of the caged mussel,Elliptio complanata, exposed to contaminated environments - Kristin E. Day; J. L. Metcalfe; S. P. Batchelor (Archives of Environmental Contamination and Toxicology, 1990)